Evaluation of an Amino Acid−Based Formula in Infants Not Responding to Extensively Hydrolyzed Protein Formula. Issue 5 (November 2016) - Vanderhoof, Jon; Moore, Nancy; de Boissieu, Delphine
Abstract : ABSTRACT: Nearly 2% to 3% of infants and children younger than 3 years have confirmed cow's milk protein allergy with multiple clinical presentations including atopic dermatitis (AD), diarrhea, and vomiting/spitting up. Although most infants with cow's milk protein allergy experience clinical improvement with the use of an extensively hydrolyzed (EH) formula, highly sensitive infants may require an amino acid−based formula. In this observational, prospective study, 30 infants (1–12 months of age) with a history of weight loss and persistent allergic manifestations while on an EH formula were provided an amino acid−based formula for 12 weeks. Mean weight gain ( z score change) improved +0.43 ± 0.28 (mean ± standard deviation) after the 12-week feeding period. Improvement was observed for many allergic symptoms including significant decreases in AD severity ( P  = 0.02). These results indicate the new amino acid–based infant formula supported healthy weight gain and improvement in allergic manifestations in infants not responding to EH formulas. Abstract : Supplemental Digital Content is available in the text